2019
DOI: 10.1016/j.compstruct.2018.11.066
|View full text |Cite
|
Sign up to set email alerts
|

A plate model for compressive strength prediction of delaminated composites

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof be al form. Please note that during the production process fore it is published in its fin errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…From the compressive static test of the [( 45 C ) 2 ,(90 C ,90 G ) 4 ,( 45 C ) 2 ] specimen, the buckled surface coming out of plane was of elliptic shape ( Figure 15 b). Propagation, which was predicted by the mathematical model [ 40 ] to occur at 6130 μstrain, was observed in the experiment at a nominal strain of approximately 5820 μstrain. Unstable propagation leading to failure did not occur until a nominal strain of 6880 μstrain.…”
Section: Resultsmentioning
confidence: 90%
“…From the compressive static test of the [( 45 C ) 2 ,(90 C ,90 G ) 4 ,( 45 C ) 2 ] specimen, the buckled surface coming out of plane was of elliptic shape ( Figure 15 b). Propagation, which was predicted by the mathematical model [ 40 ] to occur at 6130 μstrain, was observed in the experiment at a nominal strain of approximately 5820 μstrain. Unstable propagation leading to failure did not occur until a nominal strain of 6880 μstrain.…”
Section: Resultsmentioning
confidence: 90%
“…In previous research, near-surface delaminations were found to be critical for in CAI strength reduction [15,22]. Single delaminations near to surface appeared to be more severe in comparison to multiple delaminations at the interior of laminate.…”
Section: Modelling Approachmentioning
confidence: 77%
“…wherein E is the Young modulus of the material, G c is the interface fracture energy release rate, τ 0 is the maximum interfacial strength (see Table 2), and M is a model parameter which was proposed by Rice [50] It has been demonstrated that delamination size, depth location, predominat orientation, number of delaminated interfaces, as well as specimen dimensions, boundary conditions and stacking sequence affect CAI behaviour which is eventually dominated by the mechanisms of local sublaminate buckling and global laminate buckling [22,25,26,51]. It was also found that the ratio of delamination width to laminate width has a significant effect on these buckling modes [52].…”
Section: Modelling Approachmentioning
confidence: 99%
See 2 more Smart Citations